We've Got You Covered: Employer and Employee Responses to Dobbs v. Jackson - Pawel Adrjan; Svenja Gudell; Emily Nix; Allison Shrivastava; Jason Sockin; Evan Starr (Institute of Labor Economics (IZA), 2023)
Following the June 24, 2022 Dobbs v. Jackson Supreme Court ruling, which overturned the federal right to abortion established in Roe v. Wade, hundreds of employers publicly announced policies covering out-of-state employee travel for abortions and related care. Leveraging data from Indeed and Glassdoor, we first document that companies with more female and more Democratic-leaning employees and executives were more likely to announce these policies. We then examine the causal impact such announcements had on recruitment, job satisfaction, and pay by introducing a new methodology to recover similar employers who did not make announcements using workers' revealed preferences in job search. Difference-in-differences estimates reveal that for announcing companies: (i) vacancies received more job seeker interest, particularly in Democratic-leaning states and female-dominated jobs in states with "trigger" laws that outlawed abortion, (ii) satisfaction with management fell amongst existing employees, particularly in male-dominated jobs, and (iii) posted wages increased, especially for companies where employee sentiment declined. These results highlight the complicated trade-off employers face from engaging in sociopolitical dialogue, in particular how signals of company culture can help recruit new workers but alienate current ones.
Keywords: J13; J16; M14; 330; culture; abortion; politics; gender; job search; job satisfaction